Factor Xa Inhibition Reduces Coagulation Activity but Not Inflammation Among People With HIV: A Randomized Clinical Trial. (1st February 2020) - Baker, Jason V; Wolfson, Julian; Peterson, Tess; Mooberry, Micah; Gissel, Matthew; Mystakelis, Harry; Henderson, Michael W; Garcia-Myers, Kelly; Rhame, Frank S; Schacker, Timothy W; Brummel-Ziedins, Kathleen E; Sereti, Irini; et al.
Abstract: Background: Coagulation activity among persons with HIV is associated with end-organ disease risk, but the pathogenesis is not well characterized. We tested a hypothesis that hypercoagulation contributes to disease risk, in part, via upregulation of inflammation. Methods: Treatment effects of edoxaban (30 mg), a direct factor Xa inhibitor, vs placebo were investigated in a randomized, double-blind crossover trial among participants with HIV and viral suppression and D-dimer levels ≥100 ng/mL. During each 4-month crossover period, blood measures of coagulation, inflammation, and immune activation were assessed. Analyses of change on edoxaban vs change on placebo used linear mixed models. Results: Forty-four participants were randomized, and 40 completed at least 1 visit during each study period. The mean age was 49 years, and the CD4+ count was 739 cells/mm 3 . Edoxaban treatment led to declines in D-dimer (44%) and thrombin-antithrombin complex (26%) but did not lower inflammatory or immune activation measures. More bruising or bleeding events occurred during edoxaban (n = 28) than during placebo or no drug periods (n = 15). Conclusions: The direct factor Xa inhibitor edoxaban led to a substantial reduction in coagulation but no effect on inflammation or immune activation. These results do not support that hypercoagulation contributes to ongoing inflammation during chronic antiretroviral therapy–treated HIV disease. Abstract : In a randomized trial, we studied edoxaban—an inhibitor of factor X—among persons with HIV and viral suppression. Edoxaban reduced coagulation activity but had no effect on inflammation, suggesting that HIV associated hypercoagulation may not contribute to ongoing inflammation.